Preface: A Community of Players - Ruggill, Judd; Nichols, Randall James; Moeller, Ryan M.; McAllister, Ken S. (Eludamos: Journal for Computer Game Culture, 2010)
The articles in this section were initially developed for and presented at the 2010 conference of the Southwest/Texas Popular Culture Association/American Culture Association (http://swtxpca.org/). The conference, which began as a small, regional meeting in the 1970s, has since become international in scope, with upwards of a thousand presentations delivered by participants from dozens of countries. Yet despite its size, the conference maintains a friendly, casual, and intellectually robust atmosphere.